DEKONTRUKSI JUICE HIJAU BERBASIS PUDDING - Yogi wahyudin; Siti Zakiah (Media Bina Ilmiah, 2024)
Desserts are typically used as a palate cleanser,usually made from milk,cornstarch,sugar,and other ingredients,known as pudding.However,a new method for making pudding has emerged by harnessing health and sustainability trends,such as using green juice as its main ingredient.Green juice itself consists of a blend of Pakcoy,lemon,orange,and honey,rich I nutrients and fiber.The aim of this research is to revitalize the idea of traditional pudding.the research method employed experiments and conducted organoleptic tests on 30 panelists. The result of this study indicate that green juice-based can be transformed into a product tha is not only tastier but also healthier.By retaining the nutrition from green ingredients,this pudding could become an appealing alternative for costomers concerned about their health and looking to expand their dessert options.The findings of this research are expected to provide an alternative product for healthcounscious consumers